Agricultural Accounting in Livestock Companies - Yani, Ahmad; Anggraini, Ninik; Sadewa, Ega Krisna (Prosiding Seminar, 2023)
Many livestock enterprises do not prepare their financial reports in conformity with the guidelines outlined in PSAK No. 69 regarding Agriculture. This study aims to determine how PSAK No. 69 about agriculture affects profit and loss and how that affects financial statements. The research used descriptive research and a quantitative technique to examine, clarify, and draw a conclusion regarding the Application of PSAK No. 69 showed that concerning Agriculture determines revenue and its impact on financial accounts. Documentation and interviews are two data collection methods. The study's findings indicate that the company has not implemented PSAK No. 69 regarding agriculture, that its biological assets are recorded straightforwardly following the acquisition price at the time of acquisition, and that it has not adopted PSAK No. 69. buy resources that have been used up and add them. More significant income is produced for the company through PSAK No. 69 about Agriculture; the greater the payment, the higher the balance value on the balance sheet. The company's biological assets are recognized as an income by using market valuations as of the balance sheet date.